2016
DOI: 10.14791/btrt.2016.4.2.70
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection of Non-Glial Tumors in the Motor Cortex

Abstract: BackgroundDirect surgery to resect tumors in the motor cortex could improve neurological symptoms or cause novel motor weakness. The present study describes the neurological outcomes of patients after the surgical resection of non-glial tumors in the primary motor cortex.MethodsThe present study included 25 patients who had pathologically confirmed non-glial tumors in the motor cortex for which they underwent surgery. Tumor location was verified using anatomical landmarks on preoperative magnetic resonance ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Several studies have investigated rolandic meningioma cohorts and reported neurological outcomes, but they have not evaluated predictors of postoperative motor decline. Lee et al 10 described the neurological outcomes of 25 patients who had undergone resection of nonglial tumors (13 meningiomas) over the motor cortex. In their cohort, 52% had presented with preoperative deficits, which improved in 76.9% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated rolandic meningioma cohorts and reported neurological outcomes, but they have not evaluated predictors of postoperative motor decline. Lee et al 10 described the neurological outcomes of 25 patients who had undergone resection of nonglial tumors (13 meningiomas) over the motor cortex. In their cohort, 52% had presented with preoperative deficits, which improved in 76.9% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…16 Prior literature has highlighted the increased risk of postoperative morbidity for rolandic meningiomas. 10,16 However, the clinical, histological, and radiological predictors of postoperative weakness following resection of meningiomas over the motor cortex have not been reported in a larger case series. In this study, we sought to examine the rates of postoperative motor decline and to determine if there are preoperative predictors that can be used for advising patients before surgery or for considering radical debulking rather than GTR.…”
mentioning
confidence: 99%
“…Regarding BM at the sensorimotor strips, the central sulcus can be dissected to minimize brain retraction and contusion (11,32,76). Then the corticotomy was preferably established in the depth of the central sulcus overlying the tumor (32).…”
Section: Individualized Surgical Approachesmentioning
confidence: 99%
“…neurophysiology, and neurosurgical techniques, patient-tailored surgery has become the pivotal strategy in multimodal treatment paradigms of BM. However, approaching BM in the perirolandic region remains a challenge because there may be a risk of new permanent neurological deficits resulting from impairment of cortical or subcortical structure after resection of the tumors which infiltrate into the surrounding sensorimotor areas (4, [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation